Pola Manajemen Pendidikan Islam dalam Keluarga Masyarakat Kelas Menengah Kebawah Muslim: (Studi Kasus di Madrasah Aliyah Hurrasul Aqidah Kota Tarakan, Kalimantan Utara) - Nove Kurniati Sari; Zainal Abidin Muhja (MATAAZIR: Jurnal Administrasi dan Manajemen Pendidikan, 2023)
Islamic education within the family constitutes a pivotal aspect in shaping the religious identity and character of children within the Muslim community. This is particularly relevant within the context of the lower-middle-class Muslim community of Tarakan, situated in the vicinity of the Madrasah Aliyah Hurrasul Aqidah. Islamic education within the family transcends mere tradition, representing a key element in the endeavor to construct a comprehensive Islamic way of life and reinforce Islamic values within the hearts and minds of children. The research objective is to comprehend the vital role of Islamic education management within the family, particularly among the lower-middle-class Muslim community of Tarakan at Madrasah Aliyah Hurrasul Aqidah, in shaping a comprehensive Islamic way of life and cultivating the character of children deeply rooted in Islamic values. Data collection is executed through various methods, including observations, structured and unstructured interviews, as well as document collection. The data analysis process encompasses stages of data reduction, data presentation, formulation of conclusions, and validation. The subjects of this study encompass the lower-middle-class Muslim community members who practice Islam and have children enrolled in Madrasah Aliyah Hurrasul Aqidah Tarakan, School Administrative Personnel, and Class X Guardians. Meanwhile, the research focal point is the management of Islamic education within the family environment of the student's guardians. Firstly, the lower-middle-class Muslim community of Tarakan at Madrasah Aliyah Hurrasul Aqidah views Islamic education management within the family as an essential component, playing a central role in realizing a comprehensive Islamic lifestyle and shaping the character of children deeply immersed in Islamic values. The model of Islamic education management within the family among this community entails intensive interaction between parents and children, along with a comprehensive Islamic educational process. Secondly, the research also identifies factors influencing the process of Islamic education management within the family, categorized into two groups: internal factors, including the role of parents and the characteristics of children, and external factors encompassing non-nuclear family dynamics, family environment, the surrounding community, and the availability of facilities. The identification of these factors is crucial for understanding the challenges and opportunities faced by the Tarakan Muslim community in strengthening Islamic education within their families.